HUBUNGAN AKTIVITAS PENDUKUNG TERHADAP KUALITAS VISUAL KORIDOR JALAN GAJAH MADA PONTIANAK - Riesa Rizki Amalia; Bontor Jumaylinda BR Gultom; Muhammad Nurhamsyah (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2021)
This research is based on concerns about the existence of supporting activities will have an impact on the visual quality of a commercial road corridor. Activities that appear in commercial corridors are trade and service activities as well as activity support. This activity support will affect the development of the city so that it is more lively, continuous, and peaceful. In a corridor these activities can bring a lot of visitors. The large number of visitors indicates that the corridor has an attraction. The method used in this study is a method of mapping behavior and space syntax combined with questionnaires. Then the results of these data are correlated so as to know the relationship of supporting activities to the visual quality of corridors. The findings of this study are in the form of supporting activity relationship to the visual quality of the corridor of Jalan Gajah Mada Pontianak. The correlation of data between placed centered mapping and space syntax, between placed centered mapping and questionnaires, as well as between questionnaires and space syntax, showed a positive correlation. The number and position of supporting activities in the form of pkl can increase movement in an area. High movement in space syntax can indicate that the visual quality of an area has a high value. An easy-to-recognize space will attract visitors to come and supporting activities in the form of street vendors can be a movement generator and attractor.